STRATEGI WORLD UYGHUR CONGRESS (WUC) DALAM MENYUARAKAN KASUS ETNIS UYGHUR DI XINJIANG TAHUN 2014 - 2019 - Sri Upayoni, Ni Wayan; Kumala Dewi, Putu Ratih; Dharmiasih, D.A Wiwik (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
This study aims to explain WUC's strategy in voicing Uyghurs’rights. The method used in this research is a qualitative method. The background in this study are Chinese policies that discriminate against Uyghurs. Chinese government created the policy as government considered Uyghurs as a separatist group. The act of discrimination has gradually become a violation of human rights which has prompted WUC to voice this case in international forums. The Researcher use the boomerang pattern concept and tactical typology as a framework. The level of analysis used by the researcher is international system. This research then found the answer that the WUC had succeeded in building alliances with other countries and other international organizations to exert pressure on China. This success is a form of the boomerang pattern strategy and is supported by four typologies of tactics adopted by WUC. Keywords: WUC, Uyghurs, Xinjiang, Boomerang Pattern.